PROFESSOR NURBAY CABBAROV - BİNNƏTOVA, Almaz Ülvi (University Research Base, 2024)
Azerbaijani-Uzbek literary relations play an important role in the rise of Turkish literature to a new stage of development. NurbayJabbarov, Doctor of Philological Sciences, Professor is one of the Uzbek scientists who deeply understand the need for literature-aesthetics and achieved important scientific results in the study of the literature of the Turkic world; and it is remarkable to take a look at the scientific creativity of NurbayJabbarov as a close friend of Azerbaijani literature and literary criticism. He was known as a textual scholar by researching the manuscript sources of the works of Furgat, classical Uzbek writer of the 19th century and his life abroad and his creative legacy. He developed his scientific activities and conducted research in various directions: manuscript sources and textual problems; Navoi studies and theoretical issues of classical literature, studies in the field of Turkology; the research of Uzbek Jadid literature, modern Uzbek literature and current literary process. NurbayJabbarov has created remarkable research in each of these scientific fields. NurbayJabbarov made in-depth research on the literary history of the Turkic peoples. The scholar's researches such as “Literary influence and consistency in the wisdoms of Ahmed Yasevi and YunusEmre” and “Improving of the learning of HuseynJavid’s creativity in Uzbekistan” confirms this idea. The researcher's scientific studies on Jadid literature show that NurbayJabbarov is a literary critic with academic-scientific analysis experience. In the presented article, all these issues are explained in the context of the scientist's creativity. Nurbay Jabbarov's research contains remarkable scientific ideas on aruz, rhyme, balâgat (rhetoric, eloquence), fasâhat (purity and perfection of language), meani, beyan and artistic sciences, which are the philosophical-aesthetic basis of Eastern classical literature. The works of Alisher Navoiy and other poets of Uzbek classical literature are analyzed from this point of view.. All this shows that the theoretical basis of the scientist's work is solid and it is able to cater the high demands of literary studies.